How to establish current reporting of employment, hours, and earnings in developing countries - Kay, Evelyn Reis Ecker (Washington, D.C. : U.S. Dept. of Labor, Bureau of Labor Statistics, 1966)
This manual describes the method of establishing a current reporting system based on statistics of establishments concerning the number of workers employed, hours of work, and earnings.
Prepared for Agency for International Development.
Includes bibliographical references: p. 146-150.
rpm 21/02/2018
Loans
Keywords: Labor supply; Developing countries